Prey density in non-breeding areas affects adult survival of black-legged kittiwakes Rissa tridactyla - Reiertsen, Tone K.; Erikstad, Kjell E.; Anker-Nilssen, Tycho; Barrett, Robert T.; Boulinier, Thierry; Frederiksen, Morten; González-Solís, Jacob; Grémillet, David; Johns, David; Moe, Børge; Ponchon, Aurore; Skern-Mauritzen, Mette; et al. (Marine Ecology Progress Series, 2014)
In migratory birds, environmental conditions in both breeding and non-breeding areas may affect adult survival rates and hence be significant drivers of demographic processes. In seabirds, poor knowledge of their true distribution outside the breeding season, however, has severely limited such studies. This study explored how annual adult survival rates of black-legged kittiwakes Rissa tridactyla on Hornøya in the southern Barents Sea were related to temporal variation in prey densities and climatic parameters in their breeding and non-breeding areas. We used information on the kittiwakes’ spatiotemporal distribution in the non-breeding season gained from year-round light-based tracking devices (geolocators) and satellite transmitters, and kittiwake annual adult survival rates gained from a multistate capture-mark-recapture analysis of a 22 yr time series of colour-ringed kittiwakes. In the post-breeding period, kittiwakes concentrated in an area east of Svalbard, in the winter they stayed in the Grand Banks/Labrador Sea area, and in the pre-breeding period they returned to the Barents Sea. We identified 2 possible prey categories of importance for the survival of kittiwakes in these areas (sea butterflies Thecosomata in the Grand Banks/Labrador Sea area in winter and capelin Mallotus villosus in the Barents Sea in the pre-breeding season) that together explained 52% of the variation in adult survival rates. Our results may have important implications for the conservation of kittiwakes, which are declining globally, because other populations use the same areas. Since they are under the influence of major anthropogenic activities including fisheries, international shipping and the offshore oil and gas industry, both areas should be targeted for future management plans. Black-legged kittiwake · Pteropods · Capelin · Capture-mark-recapture analyses · Non-breeding distribution